2019
DOI: 10.1002/pssa.201900171
|View full text |Cite
|
Sign up to set email alerts
|

Photodetection Properties of Nonpolar a‐Plane GaN Grown by Three Approaches Using Plasma‐Assisted Molecular Beam Epitaxy

Abstract: Present work focuses on improving the quality of nonpolar a‐plane GaN thin films by introducing unconventional new efficient growth conditions without compromising their UV photodetection properties. These epitaxial thin films are grown on r‐plane sapphire using three different growth approaches by plasma‐assisted molecular beam epitaxy (PAMBE). In situ reflection high‐energy electron diffraction (RHEED) analysis is performed during and after the growth to monitor the growth mode, and it is found that the film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 32 publications
2
50
0
1
Order By: Relevance
“…These results underlined the importance of aligning the contact electrodes along the favorable azimuth direction in order to restrict the transport of the charge carriers. In a subsequent work, Pant et al [51] have further shown [48].…”
Section: Iii-nitrides-based Devicesmentioning
confidence: 83%
“…These results underlined the importance of aligning the contact electrodes along the favorable azimuth direction in order to restrict the transport of the charge carriers. In a subsequent work, Pant et al [51] have further shown [48].…”
Section: Iii-nitrides-based Devicesmentioning
confidence: 83%
“…In recent years, several attempts were accomplished to enhance the efficiency of UV photodetectors by using wide and direct bandgap semiconductor materials such as aluminum gallium nitride (AlGaN)/aluminum indium gallium nitride (AlInGaN), aluminum nitride (AlN), gallium nitride (GaN) and zinc oxide (ZnO), and other organic compounds [12,[14][15][16][17][18]; the range of the bandgaps of these materials is 0.7-6.4 eV. Thus, these materials are deemed suitable for the use of wide bandgap photodetectors [17,19,20]. However, the exciton-binding energy of these materials is 40-52 meV, resulting in a hindrance of the devices' performance [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a non-polar GaN-based photodetector would exhibit a faster response with higher efficiency. Several groups have reported the use of the non-polar growth direction to produce GaN-based photodetectors along the non-polar direction as an alternative for c-orientated photodetectors [19,23,[30][31][32]. However, it is noteworthy that non-polar GaN grown on sapphire or silicon (Si) substrates portrayed low crystal quality (far from device requirement) with a broad full width at half maximum (FWHM) of ∼0.5-0.6 • as compared to the c-orientated GaN growth (less than 0.1 • ) [2,7,19,23,30,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако этот метод не подходит для коммерческих целей из-за его низкой производительности и ограничений по размерам. Наиболее популярными способами изготовления неполярных квазиподложек является гетероэпитаксиальное выращивание неполярного GaN на чужеродных подложках с использованием осаждения из металлоорганических соединений (MOCVD) [5], метод молекулярнолучевой эпитаксии (MBE) [6] и метод хлорид-гидридной газофазной эпитаксии (HVPE) [7].…”
Section: Introductionunclassified